Cytosolic phospholipase A2 plays a crucial role in ROS/NO signaling during microglial activation through the lipoxygenase pathway. Issue 1 (December 2015) - Chuang, Dennis; Simonyi, Agnes; Kotzbauer, Paul; Gu, Zezong; Sun, Grace
Abstract Background Oxidative stress and inflammation are important factors contributing to the pathophysiology of numerous neurological disorders, including Alzheimer's disease, Parkinson's disease, acute stroke, and infections of the brain. There is well-established evidence that proinflammatory cytokines and glutamate, as well as reactive oxygen species (ROS) and nitric oxide (NO), are produced upon microglia activation, and these are important factors contributing to inflammatory responses and cytotoxic damage to surrounding neurons and neighboring cells. Microglial cells express relatively high levels of cytosolic phospholipase A2 (cPLA2 ), an enzyme known to regulate membrane phospholipid homeostasis and release of arachidonic acid (AA) for synthesis of eicosanoids. The goal for this study is to elucidate the role of cPLA2 IV in mediating the oxidative and inflammatory responses in microglial cells. Methods Experiments involved primary microglia cells isolated from transgenic mice deficient in cPLA2 α or iPLA2 β, as well as murine immortalized BV-2 microglial cells. Inhibitors of cPLA2 /iPLA2 /cyclooxygenase (COX)/lipoxygenase (LOX) were used in BV-2 microglial cell line. siRNA transfection was employed to knockdown cPLA2 expression in BV-2 cells. Griess reaction protocol was used to determine NO concentration, and CM-H2DCF-DA was used to detect ROS production in primary microglia and BV-2 cells. WST-1 assay was used to assess cell viability. Western blotting was used to assess protein expression levels. Immunocytochemical staining for phalloidin against F-actin was used to demonstrate cell morphology. Results In both primary and BV-2 microglial cells, stimulation with lipopolysaccharide (LPS) or interferon gamma (IFNγ) resulted in a time-dependent increase in phosphorylation of cPLA2 together with ERK1/2. In BV-2 cells, LPS- and IFNγ-induced ROS and NO production was inhibited by arachidonyl trifluoromethyl ketone (AACOCF3) and pyrrophenone as well as RNA interference, but not BEL, suggesting a link between cPLA2, and not iPLA2, on LPS/IFNγ-induced nitrosative and oxidative stress in microglial cells. Primary microglial cells isolated from cPLA2 α-deficient mice generated significantly less NO and ROS as compared with the wild-type mice. Microglia isolated from iPLA2 β-deficient mice did not show a decrease in LPS-induced NO and ROS production. LPS/IFNγ induced morphological changes in primary microglia, and these changes were mitigated by AACOCF3. Interestingly, despite that LPS and IFNγ induced an increase in phospho-cPLA2 and prostaglandin E2 (PGE2) release, LPS- and IFNγ-induced NO and ROS production were not altered by the COX-1/2 inhibitor but were suppressed by the LOX-12 and LOX-15 inhibitors instead. Conclusions In summary, the results in this study demonstrated the role of cPLA2 in microglial activation with metabolic links to oxidative and inflammatory responses, and this was in part regulated by the AA metabolic pathways, namely the LOXs. Further studies with targeted inhibition of cPLA2 /LOX in microglia during neuroinflammatory conditions can be valuable to investigate the therapeutic potential in ameliorating neurological disease pathology.